2009
DOI: 10.1038/npp.2009.158
|View full text |Cite
|
Sign up to set email alerts
|

A Cannabinoid CB1 Receptor Antagonist Ameliorates Impairment of Recognition Memory on Withdrawal from MDMA (Ecstasy)

Abstract: ( + /À)-3,4-Methylenedioxymethamphetamine (MDMA, 'Ecstasy') abusers have persistent neuropsychiatric deficits including memory impairments after the cessation of abuse. On the other hand, cannabinoid CB 1 receptors have been implicated in learning/memory, and are highly expressed in the hippocampus, a region of the brain believed to have an important function in certain forms of learning and memory. In this study, we clarified the mechanism underlying the cognitive impairment that develops during MDMA withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Nawata et al also showed that CB1 receptor antagonist attenuated the MDMA-induced cognitive deficit in mice [43]. Accordingly, we observed in the present study that genes involved in the regulation of memory and cognitive processes were downregulated after MDMA treatment in DA rats.…”
Section: Discussionsupporting
confidence: 72%
“…Nawata et al also showed that CB1 receptor antagonist attenuated the MDMA-induced cognitive deficit in mice [43]. Accordingly, we observed in the present study that genes involved in the regulation of memory and cognitive processes were downregulated after MDMA treatment in DA rats.…”
Section: Discussionsupporting
confidence: 72%
“…Cannabinoid CB1 receptors (CB1R) have been implicated in learning/memory, and are highly expressed in the hippocampus, a region of the brain believed to have an important function in certain forms of learning and memory. Using male CD1 wt and CB1R knockout (CB1R -/-) mice, Nawata and colleagues investigated the effect of withdrawal from repeated MDMA in an object recognition test [97]. Similar to what had been observed by others in rats [98][99][100], wt mice showed impaired recognition memory upon MDMA withdrawal.…”
Section: Ii5 Cognitive and Behavioural Impairmentsmentioning
confidence: 80%
“…There are also some reports on induced memory dysfunction by this agent remaining after abstinence. In an object recognition task, memory was significantly impaired after withdrawal of repeated, but not single administration of MDMA on 1st and especially 7th day of withdrawal period in mice (40). In a comparison among abstinent rats after chronic use of MDMA, current cannabinoid and control groups showed that abstinent MDMA animals were the worst group in memory tests (41).…”
Section: Resultsmentioning
confidence: 97%
“…In an object recognition memory task, chronic intake of AM281, a cannabinoid antagonist/inverse agonist, significantly improved the memory impairment following naloxone-precipitated morphine withdrawal in mice (73). Nawata et al (40) showed that levels of cannabinoid CB1 receptor protein increased on the 7th day of withdrawal, but not on the first day after chronic use of MDMA. Prescribing a CB1 antagonist with MDMA and AM251, for mice prevented memory deficits observed in withdrawn animals by using an objective recognition task.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation